2018
DOI: 10.1177/2325967118810772
|View full text |Cite
|
Sign up to set email alerts
|

Professional Soccer Players’ Return to Play and Performance After Operative Repair of Achilles Tendon Rupture

Abstract: Background:The majority of Achilles tendon ruptures are sports related; however, no investigation has examined the impact of surgical repair for complete ruptures on professional soccer players.Purpose:To examine the return to play, playing time, and performance of professional soccer players following Achilles tendon repair.Study Design:Cohort study; Level of evidence, 3.Methods:Union of European Football Associations (UEFA) and Major League Soccer (MLS) athletes who sustained a primary complete Achilles tend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 34 publications
2
52
1
1
Order By: Relevance
“…The mean rate of athletes being unable to RTP among the above-mentioned studies was 29.7 ± 6.738 [ 19 , 57 , 101 , 102 ], and athletes who did not return to their previous level of sport was 25.5 ± 7.5 [ 103 , 104 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean rate of athletes being unable to RTP among the above-mentioned studies was 29.7 ± 6.738 [ 19 , 57 , 101 , 102 ], and athletes who did not return to their previous level of sport was 25.5 ± 7.5 [ 103 , 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that the 70.8% of the selected soccer players were able to return to play, confirming that nearly the 30% of them (29.2%) were unable to return to play, as reported in their other above-mentioned study [ 57 ]. In any case, the major difference between the two studies is that, while in the first study professional athletes reached the same pre-injury performance 2 years post-operatively [ 57 ], in the present study, soccer players were found to play fewer minutes 2 years post-operatively compared with their baseline as well as playing less at 1 and 2 years post-operatively compared with uninjured matched controls [ 102 ]. The reduction in playing time following an Achilles repair has significant implications for professional players and teams [ 102 ].…”
Section: Return To Playmentioning
confidence: 92%
See 1 more Smart Citation
“…27 A meta-analysis comparing minimally invasive vs open repair reported an overall return to play of 78% in 422 patients, with no difference in return to sport between operative techniques. 1 Numerous studies have reported on return to play in professional athletes, including 69.4% in a group of 62 mixed sport professional athletes (National Basketball Association [NBA], National Football League [NFL], and Major League Baseball [MLB]), 38 70.8% to 82% in professional soccer players, 14,39 61% in 18 NBA players, 2 and 72% in 95 NFL players. 18 The method in which “return to play” was defined and the degree to which the same level of play vs any level of play was considered is heterogenous or unclear in these prior studies.…”
Section: Discussionmentioning
confidence: 99%
“…Following Achilles tendon rupture, return to play has been reported to be 67% to 78% in a general population and between 61% and 82% in professional athletes. 1,2,14,18,20,26,27,38,39 However, existing literature has poorly defined factors that are associated with the ability to return to play.…”
Section: Introductionmentioning
confidence: 99%